Assessing effectiveness of wood spray painting system model for undergraduate engineering education. Issue 1 (20th August 2018) - Tran, Cong Chi; Hoang, Son; Hoang, Tien Duong; Nguyen, Thi Hong Hanh
Abstract: In this study, the effectiveness of an experimental model of spray painting system (SPS) for wood products in engineering education was evaluated based on students' mental workload (MWL). The subjective rating method, NASA‐task load index (NASA‐TLX), was used to evaluate the MWL of 34 students and 8 experts. The results of the data analysis showed that the assessment of the students' MWL was higher than that of the experts. Hence, the research indicated the need to improve the practical content in order to reduce the student MWL. In addition, the results demonstrated that students' MWL could be used to consider the effectiveness of the experimental model in engineering education, thereby improving the model's efficiency and the quality of training.